A look into hallucinations: the relationship between visual imagery and hallucinations in Alzheimer's disease. Issue 4 (4th July 2019) - El Haj, Mohamad; Badcock, Johanna C.; Jardri, Renaud; Larøi, Frank; Roche, Jean; Sommer, Iris E.; Gallouj, Karim
ABSTRACT: Introduction: We investigated the relationship between visual hallucinations and vividness of visual imagery in patients with Alzheimer's disease (AD). Method: We recruited 28 patients with AD and 30 healthy control participants, matched for age and education. We evaluated proneness towards hallucinations with the Launay–Slade Hallucinations Scale, which includes items assessing visual and auditory hallucinations. We also evaluated vividness of visual imagery with the Vividness of Visual Imagery Questionnaire on which participants had to imagine four images (i.e., imagining the face of a friend, the rising sun, a familiar shop-front, and a country scene) and report the vividness of the images they generated. Results: Analysis demonstrated significant positive correlations between visual hallucinations and vividness of visual imagery in AD patients, however, no significant correlations were observed between auditory hallucinations and vividness of visual imagery in these participants. No significant correlations were observed between hallucinations and vividness of visual imagery in healthy control participants, probably due to the lack of hallucinations in these participants. Discussion: These results demonstrate a selective relationship between the occurrence of visual (but not auditory) hallucinations and the ability to generate vivid visual images in AD.